Plant level browse intensity on observation plots in Yellowstone's Northern Range, 2009-2013 - Hobbs, Tom; Kotter, Dan (Colorado State University. Libraries, 2016)
Data file and metadata sheet for column fields.
Zip file includes: data and metadata file.
Natural Resource Ecology Laboratory (NREL)
Keywords: willow; biomass; production; browse intensity